I stink! - McMullan, Kate.; McMullan, Jim, 1936- (New York : Joanna Cotler Books, 2002)
A big city garbage truck makes its rounds, consuming everything from apple cores and banana peels to leftover ziti with zucchini.
Horn Book Starred
School Library Journal starred
Wilson's Children
2.2
K-3.
K-3
Keywords: Refuse and refuse disposal -- Fiction; Refuse and refuse disposal -- Fiction